TiO2 nanoparticles incorporation in carbon nanofiber as a multi-functional interlayer toward ultralong cycle-life lithium-sulfur batteries - Yao, Shanshan; Tang, Hao; Liu, Mingquan; Chen, Lili; Jing, Maoxiang; Shen, Xiangqian; Li, Tianbao; Tan, Jinli (Journal of alloys and compounds, 2019)
Lithium-sulfur (Li-S) batteries have attracted many attentions due to their high energy density and low-cost. However, the insulation and volume change of sulfur and high solubility of polysulfides lead to the fast decay of capacity and short cycle life. In order to solve these issues, we synthesized a novel multifunctional TiO2@C composite nanofibers (TiO2@C CNs) interlayer by electrospinning technique and subsequent heat treatment. It can significantly improve the specific capacity and long cycling stability of Li-S batteries, attributed to the effective restriction of “shuttle effect” and high reutilization of trapped active materials. Using TiO2@C CNs as a multifunctional interlayer, the BP2000/sulfur cathode with a high sulfur content (70 wt %) shows an initial capacity of 852 mAh g−1 at a high current rate of 4C and cycled over 2000 cycles with a fade rate of only 0.028% per cycle. The combination of metal oxides and carbon materials is facile and feasible way to archive high performance Li-S batteries. [Display omitted] •The TiO2@C CNs was fabricated by electrospinning technique.•The mesoporous structure of TiO2@C CNs was used as the interlayer in Li-S cell.•TiO2@C CNs acts as polysulfide reservoirs to alleviate the shuttle effect.•TiO2@C CNs accelerates the electrochemical reaction kinetic during cycle process.